Analysis of Foreign Investment in Indonesia: A Case Study of Blackpink Brand Ambassador and Oreo Brand Image - Sari, Salwa Nurmala; Amelia, Farah; Sihombing, Jeciska; Natasia, Rachel; Hutasoit, Rifka; Adlina, Hafiza (International Journal of Cultural and Social Science, 2023)
Foreign direct investment has become a significant phenomenon in the global economic context, including in Indonesia. This study aims to analyze the influence of foreign direct investment on BLACKPINK's brand ambassador and Oreo's brand image in Indonesia. In this case study, we adopt a literature review approach to investigate concepts related to foreign direct investment, brand ambassadors, and brand image. In this research, we also observe the factors influencing the success of foreign direct investment and the effectiveness of brand ambassadors. Our analysis reveals that factors such as appropriate marketing strategies, alignment between the brand and the ambassador, and positive interaction between the brand and consumers play pivotal roles in achieving successful outcomes. By gaining deeper insights into the influence of foreign direct investment on BLACKPINK's brand ambassador and Oreo's brand image, this study can provide valuable insights for companies and other stakeholders in understanding the increasingly global dynamics of the Indonesian market. Furthermore, this research can serve as a foundation for developing more effective marketing strategies in the context of foreign direct investment and the utilization of brand ambassadors in the future.